2022
DOI: 10.1242/jcs.259856
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase SETD2 negatively regulates cell size

Abstract: Cell size varies between cell types but is tightly regulated by cell-intrinsic and extrinsic mechanisms. Cell-size control is important for cell function and changes in cell size are frequently observed in cancer. Here we uncover a role for SETD2 in regulating cell size. SETD2 is a lysine methyltransferase and a tumor suppressor protein involved in transcription, RNA processing and DNA repair. At the molecular level, SETD2 is best known for associating with RNA polymerase II through its Set2-Rbp1 interacting (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…Further, beyond dysregulation of common gene co-expression networks, HAR perturbations also converged on the downregulation of particular genes. Among these was SETD2 , a chromatin remodeler and cytosolic modifier of tubulin which has previously been shown to contribute to neuronal cell polarity, and whose knockdown has been found to contribute to increased translational output, migratory gene expression, and disrupted NSC lamination, phenotypes which are consistent with our results 6669,87,88 . Another gene downregulated by several HAR perturbations was PCM1 , and important regulatory of epithelial cell structure and the timing of neurogenesis, as well as mitotic spindle orientation, a process known to coordinate the emergence of basal cortical progenitors from aRG 71,89 .…”
Section: Discussionsupporting
confidence: 92%
“…Further, beyond dysregulation of common gene co-expression networks, HAR perturbations also converged on the downregulation of particular genes. Among these was SETD2 , a chromatin remodeler and cytosolic modifier of tubulin which has previously been shown to contribute to neuronal cell polarity, and whose knockdown has been found to contribute to increased translational output, migratory gene expression, and disrupted NSC lamination, phenotypes which are consistent with our results 6669,87,88 . Another gene downregulated by several HAR perturbations was PCM1 , and important regulatory of epithelial cell structure and the timing of neurogenesis, as well as mitotic spindle orientation, a process known to coordinate the emergence of basal cortical progenitors from aRG 71,89 .…”
Section: Discussionsupporting
confidence: 92%
“…Molenaar et al. recently reported that overexpression of the SRI domain significantly inhibited H3K36me3 and enlarged cell size ( 16 ).…”
Section: Protein Structure Of Setd2mentioning
confidence: 99%